New insights into the mechanisms of the immune microenvironment and immunotherapy in osteosarcoma - Luo, Cong; Min, Xingxing; Zhang, Danying (Frontiers in Immunology, 2025)
Osteosarcoma, a malignant bone tumor primarily affecting adolescents, is highly invasive with a poor prognosis. While surgery and chemotherapy have improved survival for localized cases, pulmonary metastasis significantly reduces survival to approximately 20%, highlighting the need for novel treatments. Immunotherapy, which leverages the immune system to target osteosarcoma cells, shows promise. This review summarizes the biological characteristics of osteosarcoma, mechanisms of pulmonary metastasis, and the tumor immune microenvironment (TME). It involves recent immunotherapy advances, including monoclonal antibodies, tumor vaccines, immune cell therapies, checkpoint inhibitors, and oncolytic viruses, and discusses combining these with standard treatments.